ASSESSMENT OF INFRASTRUCTURE PROJECTS DEVELOPMENT DYNAMICS - Parvin Alasgarli (Foundations and Trends in Modern Learning, 2024)
The article contains information about the infrastructure projects implemented in the Republic of Azerbaijan in recent years and their results. At this time, analyzes were conducted using various sources. Based on the obtained results, it was determined that economic development was clearly observed as a result of infrastructure projects implemented in the regions and Baku city in recent times.